Being there again – Presence in real and virtual environments and its relation to usability and user experience using a mobile navigation task - Brade, Jennifer; Lorenz, Mario; Busch, Marc; Hammer, Niels; Tscheligi, Manfred; Klimant, Philipp (International journal of human-computer studies, 2017)
The possibility of using virtual environments instead of real field or laboratory environments is a promising research field. However, before virtual environments are able to replace the traditional environments the differences between the methods must be worked out. We take up on previous studies which compared different real and virtual environments concerning presence and usability and expand the research on the factor of user experience. We compared a virtual field environment (CAVE – Cave Automatic Virtual Environment) and a real field environment (city center of Chemnitz, Germany) in a between-subject-design concerning presence, and evaluate its impact on the usability and the user experience of a geocaching game. The data of 60 participants was analyzed and shows significantly higher ecological validity for the real field environment but higher values for engagement and negative effects in the virtual field environment. Concerning usability, significant differences were verified between the two environments. All presence factors correlated significantly with usability in the CAVE, but did not correlate in the real-field environment. Concerning user experience, the CAVE showed significantly higher hedonic quality values, whereas the real field environment had higher pragmatic quality values. In both conditions presence and user experience factors were partly correlated. Our results indicate that virtual environments can be an alternative to real environments for user experience studies, when a high presence is achieved. •virtual environments are an alternative for user experience studies.•Ratings for usability are correlated with presence in VR.•Ratings for user experience are correlated with presence in VR.